Aplikasi Notifikasi Telegram Untuk Mengetahui Trend Forex Trading Dengan Menggunakan Pola Japanese Candlestick - Ricky Kuncoro; Agustinus Noertjahyana; Justinus Andjarwirawan (Jurnal Infra, 2020)
Forex Trading is a business that promises high profit and freedom such as not needing big capital and a physical office. However, the reality is that not every trader can take a satisfying profit because of not realizing changes of trend direction in a market. Because of that, there needs to be an application that is capable of telling when there will be a change of trend direction on the market in real-time so that a trader can maximize the potential to take advantage of a large amount of profit.Expert Advisor is used as a reading of a change of trend direction automatically and inside it has a method to read the direction of market trend, which is called Japanese Candlestick. There are many types of Japanese Candlestick Pattern that already exist however in this research there will be 4 patterns that will be used, which are Hammer Pattern, Doji, Engulfing, and Custom. Then, Telegram will be used as chatbot to notify users of a change in trend direction.Testing result has proved in EUR/USD currencies in time frame H4 that the application that was made was capable of reading reversal trend of average 44,76% and continuation trend of average 67,60% in three years. To deliver the notification on Telegram, Expert Advisor will generate the reading of trend direction using Japanese Candlestick in file form for the chatbot in Telegram which will use Python programming language to get the file. Then the  chatbot will read and send the file of the reading result in  notification form to Telegram users.